2014
DOI: 10.1186/s13046-014-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

The expression profile of Dopamine D2 receptor, MGMT and VEGF in different histological subtypes of pituitary adenomas: a study of 197 cases and indications for the medical therapy

Abstract: BackgroundTo study the expression of D2R, MGMT and VEGF for clinical significance in pituitary adenomas, and to predict the potential curative medical therapy of dopamine agonists, temozolomide and bevacizumab on pituitary adenomas.MethodsImmunohistochemistry and western blot were performed to detect the expression of expression of D2R, MGMT and VEGF in pituitary adenoma tissue samples. The ratio of high expression of D2R, MGMT or VEGF in different subtypes of PA was compared by the use of chi-squared tests. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“…The tissues consisted �� 24 ���l�c���-��c�����g ��������, 24 Immunohistochemical staining. A streptavidin-peroxidase method was used for immunostaining, as previously described (12). Briefly, slides were deparaffinized with xylene ����� ����� (��� 5-10 ��� ��c�), ���������� ����� ����� �� � gradient series of ethanol (100, 95 and 75%), and rinsed with phosphate-buffered saline (PBS).…”
Section: Pa Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissues consisted �� 24 ���l�c���-��c�����g ��������, 24 Immunohistochemical staining. A streptavidin-peroxidase method was used for immunostaining, as previously described (12). Briefly, slides were deparaffinized with xylene ����� ����� (��� 5-10 ��� ��c�), ���������� ����� ����� �� � gradient series of ethanol (100, 95 and 75%), and rinsed with phosphate-buffered saline (PBS).…”
Section: Pa Sample Collectionmentioning
confidence: 99%
“…The slides were independently evaluated by two investigators under a light microscope (TE200; Nikon, Tokyo, Japan). As described previously (12), the staining intensity was scored as follows: 0, negative; 1, weak; 2, medium; and 3, strong. The extent of staining was scored as follows: 0, 0%; 1, 1-25%; 2, 26-50%; 3, 51-75%; and 4, 76-100%, according to the percentages of the positive staining area in relation to the whole carcinoma area.…”
Section: Pa Sample Collectionmentioning
confidence: 99%
“…On the other hand, in a RT-PCR study of different subtypes of pituitary adenomas, somatotropinomas showed lowest VEGF expression [29,30]. In IHC, expression of VEGF was decreased in somatotropinomas, against normal tissue [31].…”
Section: Prace Oryginalnementioning
confidence: 93%
“…Em nossa casuística, 63% das amostras de somatotropinomas expressaram DRD2 de forma moderada ou intensa (IRS ≥ 4), confirmando dados anteriormente publicados (176) . A eficácia da CAB no controle hormonal foi obtida em 30% dos somatotropinomas, compatível com os dados da literatura (72) .…”
Section: Discussionunclassified
“…A expressão frequente de DRD2 em ACNF também foi relatada anteriormente (155,159,176) , no entanto, sua correlação com resposta à CAB foi avaliada estatisticamente por apenas dois estudos (153,155) , sendo positiva em apenas um deles (153) .…”
Section: Discussionunclassified